A study protocol of the additional human albumin during resuscitation in patients with surgical septic shock: A randomized controlled trial (the ALBumin Use in Surgical septic shock, ALBUS study) - Nattachai Hemtanon; Nuanprae Kitisin; Thassayu Yuyen; Nattaya Raykateeraroj; Patipan Toomtong; Prasert Sawasdiwipachai; Onuma Chaiwat; Annop Piriyapatsom; Karuna Wongtangman; Nonthida Rojanapithayakorn; Suchanun Lao-amornphunkul; Thirada Srinil; et al. (Clinical Critical Care, 2026)
Background: Surgical septic shock has a high mortality rate, which increases further in patients with low serum albumin levels. Current guidelines recommend crystalloids for initial fluid resuscitation, but excessive fluid administration can lead to complications such as volume overload and intra-abdominal hypertension. Human albumin solution (HA) may have benefits due to its oncotic properties, anti-inflammatory effects, and stabilization of the vascular endothelium. The latter may result in reduced mortality and improve clinical outcomes compared to standard care. Methods: This single-center, open-labeled, randomized controlled trial is conducted in surgical intensive care units (ICU) at Siriraj Hospital, Bangkok, Thailand. The patients admitted with confirmed or suspected surgical infection within 48 hours and fulfilling Sepsis-3 criteria for septic shock are enrolled. Patients are randomized at 1:1 to receive either protocolized 20% HA as an adjunct to standard care or standard care alone. The intervention is administered for 72 hours. The primary outcome is 28-day all-cause mortality. Secondary outcomes are hospital length of stay (LOS), ICU LOS, days alive and free of vasopressors and mechanical ventilation, cumulative 7-day fluid balance, rate of acute kidney injury requiring renal replacement therapy, and gastrointestinal function recovery. A total of 304 patients (152 per group), accounting for an estimated 10% dropout rate, is required. Analysis follows intention-to-treat principles. Hypothesis: We hypothesized that adding 20% HA to standard care would improve clinical outcomes compared with standard care alone. Conclusions: The ALBUS trial is the randomized controlled trial designed specifically to evaluate the addition of 20% HA to standard care during resuscitation in surgical septic shock. We aim to provide evidence to support the use of HA as an adjunctive resuscitation in reducing 28-day mortality and improving clinical outcomes in the surgical population. Ethics and dissemination: This trial received approval from the Siriraj Institutional Review Board. Trial registration: NCT07212582